The Effect of Outdoor Learning Method on Indonesian Language Learning Outcomes in Descriptive Text Material Among Fifth-Grade Elementary Students - Muliadi, Muliadi; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
Abstract The learning process was still dominated by lecture-based methods, causing students to become passive and less engaged in classroom activities. The Outdoor Learning method was selected as an alternative instructional approach that utilizes the surrounding environment to enhance student involvement and comprehension. This study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The sample consisted of two classes: class VA as the experimental group (20 students) who received instruction using the Outdoor Learning method, and class VB as the control group (18 students) who were taught using the lecture method. Data were collected through pretests and posttests, as well as through observations of student activity. The pretest results showed that both the experimental and control groups had the same average score of 81. The experimental group had a highest score of 97 and a lowest of 65, while the control group ranged from 94 to 61. This indicated that both groups had comparable initial abilities. After the intervention, the average posttest score of the experimental group increased to 88 (with scores ranging from 74 to 100), while the control group increased to 82 (ranging from 65 to 94). A t-test on the posttest data yielded a significance value (Sig. 2-tailed) of 0.039 < 0.05, indicating a statistically significant difference in student learning outcomes between the two groups. The findings suggest that the Outdoor Learning method had a positive and significant effect on improving student learning outcomes. In addition to the increase in scores, classroom observations also revealed an improvement in students’ learning activities in the experimental group, particularly in cooperation, responsibility, and the confidence to express opinions. The Outdoor Learning method is a viable alternative for implementing active and meaningful learning strategies, especially in developing descriptive text skills at the elementary level